Earth System Modelling - Volume 3 Coupling Software and Strategies - Valcke, Sophie; Redler, René.; Budich, Reinhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Collected articles in this series are dedicated to the development and use of software for earth system modelling and aims at bridging the gap between IT solutions and climate science. The particular topic covered in this volume addresses the major coupling software developed and used in the climate modelling community.
Coupling Software and Strategies -- TDT - A Library for Typed Data Transfer -- The Model Coupling Toolkit -- The OASIS Coupler -- The Flexible Modeling System -- The Earth System Modeling Framework -- The Bespoke Framework Generator -- Future Perspectives.
Keywords: Earth sciences; Software engineering; Earth Sciences, general; Software Engineering